2019
DOI: 10.1007/s12144-019-00309-7
|View full text |Cite
|
Sign up to set email alerts
|

A test of theory of planned behavior in type II diabetes adherence: The leading role of perceived behavioral control

Abstract: Diabetes mellitus is a health complication that millions of people suffer from all over the world. Type II (non-insulin dependent) diabetes requires many changes in the daily lives of patients, including monitoring blood glucose, following a healthy diet, exercising, and taking medications. Although it is vital for their health, patients generally find it difficult to adhere to their medical regimen. In order to better understand the adherence behaviors of type II diabetes patients, the theory of planned behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
0
13
0
2
Order By: Relevance
“…Family empowerment has the influence and effectiveness to increase family independence and client adherence to therapy and diet programs. The family empowerment referred to in this article is family empowerment based on the theory of planned behavior 28 , and family empowerment is based on analysis of client and family background factors 18 , personal factors 14 , social factors, and information factors from the family of patients suffering from DM 33 . The use of behavior change based on a protocol will encourage others to understand and understand important aspects and a sense of responsibility for what has been done in self-care efforts 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family empowerment has the influence and effectiveness to increase family independence and client adherence to therapy and diet programs. The family empowerment referred to in this article is family empowerment based on the theory of planned behavior 28 , and family empowerment is based on analysis of client and family background factors 18 , personal factors 14 , social factors, and information factors from the family of patients suffering from DM 33 . The use of behavior change based on a protocol will encourage others to understand and understand important aspects and a sense of responsibility for what has been done in self-care efforts 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Family empowerment carried out by health workers must also pay attention to the multiculture in a patient and family such as social, cultural, demographic, financial and other supporting factors 42 . The use of family empowerment will optimally improve treatment if family independence is carried out with a more holistic approach to managing diabetes mellitus adherence behaviors, taking into account the socio-cultural dynamics that occur in many medical conditions 28 .…”
Section: Discussionmentioning
confidence: 99%
“…www.ijacsa.thesai.org was in the tobacco belt, which may affect the reactions of the participants, and the study measured the smoking behaviors before the campaign only, it did not measure it after the campaign. The authors in [35] targeted the type two diabetes patients, but the study did not take the patient's diversity into account and the social desirability bias might affect the accuracy of the data. The authors in [36] targeted the cervical cancer patients, but the study did not employ an experimental design to establish the causal effect relations among variables.…”
Section: B Health Behavior Change Models Applicationsmentioning
confidence: 99%
“…The authors in [34][35][36] used TPB in their studies. The authors in [34] targeted the smokers, but the implementation (IJACSA) International Journal of Advanced Computer Science and Applications, Vol.…”
mentioning
confidence: 99%
“…Seaborn et al (2016) showed that perceived behavior control is a strong predictor of the possibility of adopting type 2 diabetes preventive behavior. Dilekler et al (2019) stated the importance of perceived behavior control of adherence to monitoring blood glucose, following a healthy diet, exercising, and taking medication, so perceived behavior control is important when considering interventions for type 2 diabetes patients. Wongrith (2019) stated that perceived behavior control is the most important factor that predicts the intention and behavior of self-care management, reinforced by Menti et al (2019) showed self-efficacy in SCT to be most effective for influencing behavioral changes in terms of increasing medication adherence, diet and physical exercise for people with type 2 diabetes when combined with goal setting practices.…”
Section: The Effect Of Perceived Behaviormentioning
confidence: 99%